Computational hemodynamic assessment of axillary and femoral artery perfusion for extracorporeal left ventricular assist device - Wang, Shilin; Liu, Qianwen; Li, Ping; Zhang, Changdong; Wu, Wenqian; Liu, Hao; Yang, Peiwen; Fang, Lingyun; Su, Wei; Karimov, Jamshid H.; Dong, Nianguo; Chen, Shu (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesTraditionally, the arterial blood perfusion tube for an extracorporeal left ventricular assist device (LVAD) is placed in the femoral artery, which limits patients' mobility and increases the possibility of lower limb ischemia. We have also developed a new approach for percutaneous placement using the right jugular vein and axillary artery. However, there hasn't been a direct hemodynamic comparison between axillary and femoral perfusion. Therefore, this study estimated the hemodynamic differences between axillary artery and traditional femoral artery perfusion for LVAD.MethodsFive patients underwent LVAD implantation through the right axillary artery and jugular vein approach at Wuhan Union Hospital. Based on one of their computed tomographic angiography (CTA) data, we established a computational fluid dynamics model. Key hemodynamic parameters, including time-averaged wall shear stress (TAWSS) and oscillatory shear index (OSI), were estimated to be compared.ResultsThe axillary perfusion improved perfusion to critical arteries and maintained more stable blood flow distribution, regardless of whether the LVAD supplied 40% or 60% of the total cardiac output. Femoral perfusion caused a substantial reduction in TAWSS and an increase in OSI, suggesting greater blood flow disturbances. In contrast, axillary perfusion maintained TAWSS values closer to normal and exhibited lower OSI, particularly in the thoracic and upper abdominal aorta.ConclusionsThe axillary approach may offer superior hemodynamic performance compared with the conventional femoral approach for percutaneous LVAD, including improved perfusion of abdominal aortic branches and steadier blood flow changes. The jugular-axillary approach could be a promising procedure for future percutaneous LVAD.